Preparation method, product and application of a bimetallic CuCoO2 heterogeneous fenton-like catalyst material
Patent Information
- Application Number
- CN202611491726.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-23
- Publication Date
- 2026-10-30
AI Technical Summary
单金属Cu、Co催化剂反应过程中易流失、生成沉淀,利用率低
(1)本发明将Cu源(Cu(NO3)2·3H2O)、Co源(Co(NO3)2·6H2O)、碱(NaOH)和水混合后采用水热方法制备CuCoO2,条件温和、操作简单,催化降解污染物效果显著,稳定性强,具有可调变的金属价态、丰富氧空位与优异电子传导性。
Smart Images

Figure CN122999201A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the fields of composite material preparation technology and groundwater treatment technology, and in particular to a method for preparing, a product of, and the application of a bimetallic CuCoO2 heterogeneous Fenton-like catalyst material. Background Technology
[0002] Currently, groundwater organic pollution remediation methods are mainly divided into ex-situ remediation and in-situ remediation methods. A typical ex-situ remediation technology is pump-and-treatment remediation, a traditional groundwater treatment technology that was widely used as early as the 1980s. It involves deploying pumping wells to extract groundwater and then using conventional water treatment technologies for remediation. However, this method is costly and difficult to treat pollutants for extended periods, thus it is only suitable for small-scale contaminated water bodies. In-situ remediation technology, on the other hand, is considered promising due to its thorough remediation and relatively lower cost, and therefore has been widely applied to the remediation of groundwater organic pollution.
[0003] Traditional Fenton or Fenton-like systems can generate hydroxyl radicals to degrade organic pollutants. However, traditional Fenton systems usually require acidic conditions, while natural groundwater is mostly a near-neutral or weakly alkaline environment, which limits the reaction efficiency. At the same time, there are also problems such as low H2O2 utilization, metal ion residue, iron sludge generation, and secondary pollution. Therefore, traditional Fenton technology cannot be directly used for groundwater remediation.
[0004] Natural groundwater buffer systems are characterized by near-neutral to weakly alkaline pH, with bicarbonate (HCO3-) ions present. - HCO3 is a buffer ion commonly found in groundwater. According to the latest groundwater quality survey data, the HCO3 content in groundwater in the upper reaches of the Yellow River is... - The concentration of HCO3 in groundwater along the Yellow River in Henan Province ranges from 24.41 to 652.91 mg / L. - The concentration range is 1647~741.2 mg / L. Traditionally, it is believed that high concentrations of free HCO3-... - This will consume the •OH generated in the reaction system, leading to a decrease in pollutant removal rate. However, in heterogeneous Fenton-like systems, the introduction of a solid metal-based catalyst, HCO3... - No longer solely used as a hydroxyl radical quencher; HCO3 - It can react with H2O2 in the system to produce peroxymonocarbonate (HCO4). - And further convert to CO3• - It reacts with active species such as •OH. Therefore, if highly efficient catalytic materials are prepared to construct a heterogeneous Fenton-like system adapted to the groundwater environment, it can promote the reaction of HCO4- and other reactive species. - The generation and activation of [the substance] directly utilizes naturally coexisting bicarbonates in groundwater as a co-oxidizing component to achieve efficient degradation of organic pollutants.
[0005] Existing catalytic materials are mostly Cu or Co-based single-metal or bimetallic catalysts. Single-metal Cu and Co catalysts are prone to loss and precipitation during the reaction, resulting in low utilization. In contrast, Cu-Co bimetallic catalysts... + With Cu 2+ Co 2+ With Co 3+ The low valence state conversion rate leads to hindered electron transfer and decreased catalytic efficiency. Therefore, there is an urgent need to provide a catalyst material that can efficiently degrade organic pollutants in groundwater. Summary of the Invention
[0006] The purpose of this invention is to provide a method for preparing a bimetallic CuCoO2 heterogeneous Fenton-like catalyst material, its product, and its application. This bimetallic CuCoO2 heterogeneous Fenton-like catalyst material (hereinafter referred to as: CuCoO2 catalyst material) possesses a pure crystalline structure of copper-iron ore (ABO2), exhibits strong chemical stability, resistance to acids and alkalis, high temperature resistance, and is not prone to structural collapse. It also possesses tunable metal valence states, abundant oxygen vacancies, and excellent electronic conductivity, thereby better improving the catalytic material's ability to degrade pollutants. This invention also constructs a CuCoO2 / H2O2 / NaHCO3 system for in-situ oxidative degradation of organic pollutants in groundwater.
[0007] To achieve the above objectives, the present invention provides the following solution: One of the technical solutions of this invention is a method for preparing a bimetallic CuCoO2 heterogeneous Fenton-like catalyst material, comprising the following steps: The bimetallic CuCoO2 heterogeneous Fenton-like catalyst material is obtained by mixing Cu source, Co source, alkali and water and carrying out a hydrothermal reaction.
[0008] In a preferred embodiment of the present invention, the Cu source is Cu(NO3)2·3H2O.
[0009] In a preferred embodiment of the present invention, the Co source is Co(NO3)2·6H2O.
[0010] In a preferred embodiment of the present invention, the alkali is NaOH.
[0011] In a preferred embodiment of the present invention, the molar ratio of the Cu source, Co source and alkali is 1:1:(8~8.5); the ratio of the Cu source to the water is 15 mmol:(50~70) mL.
[0012] In a preferred embodiment of the present invention, the hydrothermal reaction conditions are set as follows: 120~180℃ for 6~12h.
[0013] The second technical solution of the present invention is a bimetallic CuCoO2 heterogeneous Fenton-like catalyst material prepared by the above preparation method.
[0014] The third technical solution of this invention is the application of the above-mentioned bimetallic CuCoO2 heterogeneous Fenton-like catalyst material in the in-situ oxidative degradation of organic pollutants in groundwater, wherein the HCO4 in the groundwater... - The concentration is 500~700mg / L; bimetallic CuCoO2 heterogeneous Fenton catalyst material and H2O2 are added to the groundwater to achieve in-situ oxidative degradation of organic pollutants in the groundwater.
[0015] Compared with the prior art, the present invention has the following beneficial effects: (1) In this invention, CuCoO2 is prepared by mixing Cu source (Cu(NO3)2·3H2O), Co source (Co(NO3)2·6H2O), alkali (NaOH) and water using a hydrothermal method. The conditions are mild, the operation is simple, the catalytic degradation of pollutants is significant, the stability is strong, and it has a tunable metal valence state, abundant oxygen vacancies and excellent electronic conductivity.
[0016] (2) The CuCoO2 / H2O2 / NaHCO3 system constructed in this invention activates HCO4 through CuCoO2 catalysis. - It generates active species such as carbonate free radicals and hydroxyl free radicals to degrade organic pollutants, effectively broadening the scope of application of the process and making it suitable for neutral to weakly alkaline groundwater environments.
[0017] (3) The CuCoO2 prepared by this invention is a pure crystalline bimetallic oxide of copper-iron ore ABO2. However, ordinary single-metal Cu-based and Co-based catalysts, as well as non-copper-iron ore crystalline Cu-Co composite oxide catalysts (such as spinel CuCo2O4: spinel CuCo2O4 is prepared by dissolving 15 mmol of copper nitrate and 30 mmol of cobalt nitrate in 50 mL of water at a Cu:Co molar ratio of 1:2, adding urea, and then hydrothermally reacting at 180℃ for 12 h. The resulting precipitate is washed, dried, and then calcined at 400℃ for 3 h). Under the same experimental conditions, pollutant degradation experiments were conducted, and the results showed that single-metal Cu-based and Co-based catalysts, as well as the spinel CuCo2O4 catalyst, had almost no degradation effect on pollutants. This catalyst CuCoO2 can selectively and efficiently activate peroxymonocarbonate HCO4. - HCO4 - The activation conversion rate is significantly higher than that of existing copper-cobalt based Fenton catalysts. In conventional catalytic systems, high concentrations of bicarbonate ions quench hydroxyl radicals, resulting in a significant reduction in pollutant degradation activity; however, the CuCoO2 / H2O2 / NaHCO3 system of this invention can withstand high HCO3 concentrations in groundwater. -Under environmental conditions, the catalytic activity is not inhibited by bicarbonate ions, and it can still maintain a high degradation efficiency of organic pollutants, including naturally occurring HCO3 in groundwater. - The technology transforms impurities by free radical quenching into synergistic oxidative components, an effect that is unpredictable by existing catalysts of the same type. Attached Figure Description
[0018] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0019] Figure 1 The image shows the XRD diffraction pattern of the CuCoO2 catalytic material prepared in Example 1.
[0020] Figure 2 The image shows a SEM image of the CuCoO2 catalytic material prepared in Example 1.
[0021] Figure 3 CuCoO2 / H2O in Example 2 2 / Proof of HCO4 under NaHCO3 system - The generated NMR spectrum.
[0022] Figure 4 In Example 3, p-nitroaniline (PNA) was used as a probe to detect carbonate radicals (CO3•). - The generated graph.
[0023] Figure 5 To conduct research on carbonate free radicals (CO3•) in Example 3 - The degradation effect diagram of the quenching experiment.
[0024] Figure 6 The graph shows the degradation effect of CuCoO2 catalytic material on doxycycline hydrochloride in contaminated groundwater under different systems in Example 4.
[0025] Figure 7 The graph shows the degradation effect of different amounts of CuCoO2 catalyst material on doxycycline hydrochloride in contaminated groundwater in Example 5. Detailed Implementation
[0026] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0027] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Any stated value or intermediate value within a stated range, as well as each smaller range between any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0028] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.
[0029] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.
[0030] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.
[0031] This invention constructs a CuCoO2 / H2O2 / NaHCO3 system for the in-situ oxidative degradation of organic pollutants in groundwater. This system uses CuCoO2 as a heterogeneous catalyst to promote the reaction of H2O2 and HCO3. - The reaction generates and activates peroxymonocarbonate (HCO4). - , generating carbonate free radicals (CO3• - It utilizes reactive species such as hydroxyl radicals (•OH) to achieve efficient degradation of organic pollutants in groundwater, representing a novel in-situ chemical oxidation technology.
[0032] The first aspect of this invention provides a method for preparing a bimetallic CuCoO2 heterogeneous Fenton-like catalyst material, comprising the following steps: The bimetallic CuCoO2 heterogeneous Fenton-like catalyst material is obtained by mixing Cu source, Co source, alkali and water and carrying out a hydrothermal reaction.
[0033] In a preferred embodiment of the present invention, the Cu source is Cu(NO3)2·3H2O.
[0034] In a preferred embodiment of the present invention, the Co source is Co(NO3)2·6H2O.
[0035] In a preferred embodiment of the present invention, the alkali is NaOH.
[0036] In a preferred embodiment of the present invention, the molar ratio of the Cu source, Co source and alkali is 1:1:(8~8.5). In this invention, the reason for limiting the amount of alkali to the above-mentioned ratio range is that NaOH acts as both a precipitant and a mineralizer. This ratio can directionally prepare pure phase copper-iron ore CuCoO2. If the alkali molar ratio is less than 8, incomplete precipitation and impurity phases are likely to occur; if it is greater than 8.5, impurity phases such as CuO and Co3O4 are likely to be generated, both of which will reduce the catalytic performance. Therefore, the preferred alkali dosage range in this invention is the above-mentioned ratio range.
[0037] The ratio of the Cu source to the water is 15 mmol: (50~70) mL.
[0038] In a preferred embodiment of the present invention, the conditions for the hydrothermal reaction are set as follows: reaction at 120~180℃ for 6~12h; optionally, the temperature of the hydrothermal reaction is 120℃, 130℃, 140℃, 150℃, 160℃, 170℃, 180℃ or any value between the two aforementioned values; the time of the hydrothermal reaction is 6h, 7h, 8h, 9h, 10h, 11h, 12h or any value between the two aforementioned values.
[0039] In this invention, excessively low hydrothermal temperature or too short a time can lead to incomplete crystal phase development and an increase in impurity phases; excessively high temperature or too long a time can easily cause crystal agglomeration and growth, both of which reduce catalyst activity. Therefore, this invention preferably limits the hydrothermal reaction temperature and time to the range of parameters mentioned above.
[0040] After the hydrothermal reaction is completed, the process further includes filtration, washing, drying, and grinding the filtered product. The drying temperature is 50-70°C, and the drying time is 6-12 hours. The product is ground to a particle size of 200-300 mesh, more preferably 170-230 mesh, and even more preferably 190-210 mesh.
[0041] A second aspect of the present invention provides a bimetallic CuCoO2 heterogeneous Fenton-like catalyst material prepared by the above-described preparation method.
[0042] A third aspect of this invention provides the application of the above-mentioned bimetallic CuCoO2 heterogeneous Fenton-like catalyst material in the in-situ oxidative degradation of organic pollutants in groundwater, wherein the groundwater contains HCO4 -The concentration is 500~700mg / L; bimetallic CuCoO2 heterogeneous Fenton catalyst material and H2O2 are added to the groundwater to achieve in-situ oxidative degradation of organic pollutants in the groundwater.
[0043] In a preferred embodiment of the present invention, the concentration of the bimetallic CuCoO2 heterogeneous Fenton-like catalyst material added to the groundwater is 100~600 mg / L, and the concentration of H2O2 added to the groundwater is 10~100 mM.
[0044] In a preferred embodiment of the present invention, the organic pollutant is doxycycline hydrochloride.
[0045] This invention utilizes HCO3 in groundwater - Adding H2O2 and CuCoO2, a CuCoO2 / H2O2 / NaHCO3 system is constructed to activate peroxymonocarbonate HCO4. - , generating carbonate free radicals (CO3• - Active species such as hydroxyl radicals (•OH) degrade organic pollutants in water.
[0046] The CuCoO2 prepared using the method of this invention possesses a pure crystalline structure of copper-iron ore (ABO2) and exhibits strong chemical stability. It is resistant to acids and alkalis, withstands high temperatures, and is not prone to structural collapse. CuCoO2 possesses tunable metallic valence states, abundant oxygen vacancies, and excellent electronic conductivity. Groundwater contains HCO3-. - This invention constructs a CuCoO2 / H2O2 / NaHCO3 system for the in-situ oxidative degradation of organic pollutants in groundwater. This system uses CuCoO2 as a heterogeneous catalyst to promote the reaction of H2O2 and HCO3. - The reaction generates and activates peroxymonocarbonate (HCO4). - , generating carbonate free radicals (CO3• - It utilizes reactive species such as hydroxyl radicals (•OH) to achieve efficient degradation of organic pollutants in groundwater, representing a novel in-situ chemical oxidation technology.
[0047] Unless otherwise specified, the technical solutions described in this invention are all conventional solutions in the field, and the reagents or raw materials used are all purchased from commercial channels or are publicly available unless otherwise specified.
[0048] The technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0049] Example 1 15 mmol Cu(NO3)2·3H2O, 15 mmol Co(NO3)2·6H2O, and 5 g NaOH were mixed with 50 mL of water in a molar ratio of 1:1:8.3. The mixture was stirred at 800 rpm for 30 min until the solution became homogeneous. Then, it was placed in a homogeneous reactor and hydrothermally reacted at 180 °C for 12 h to obtain a mixture. The mixture was first filtered, and then the filtered product was washed three times with distilled water to remove impurities. It was then placed in a vacuum drying oven and dried at 60 °C for 8 h. The dried product was then ground and passed through a 200-mesh sieve to obtain the CuCoO2 catalyst material.
[0050] Example 2 Samples were taken from contaminated groundwater (under dark, room temperature conditions; the main components were the contaminating antibiotic (chlortetracycline) and 600 mg / L HCO3). - Add 200 ml of the solution to a beaker, along with 40 mM H2O2 and 400 mg / L CuCoO2 at room temperature. Stir at 800 rpm for 30 min, then take a sample of the solution to test for HCO3-. - Does HCO4 form? - .
[0051] Example 3 A sample of contaminated groundwater A was taken (under dark, room temperature conditions; the main components were the contaminating antibiotic (chlortetracycline) and 600 mg / L HCO3). - Add 200 ml of H2O2 to a beaker at room temperature, then add 40 mM H2O2 all at once (no further additions are needed). Add 400 mg / L CuCoO2 and stir at 800 rpm for 30 min. Use p-nitroaniline (PNA) as a probe to detect carbonate radicals (CO3•). - The generation of HCO3 was detected by sampling at 0 min, 60 min, 90 min, and 120 min. Then, samples without HCO3 were collected. - The contaminated groundwater B (which differs from the contaminated groundwater A mentioned earlier only in that it lacks HCO3) - The same experiment was conducted, compared with the experiment without HCO3. - The differences in pollutant degradation between the system (using contaminated groundwater B) and the synergistic system (using contaminated groundwater A) were investigated. The degradation of carbonate free radicals (CO3•) was also studied. - Quenching experiment.
[0052] Example 4 Three samples of contaminated groundwater were taken separately (under dark, room temperature conditions; the main components were the contaminating antibiotic (chlortetracycline) and 600 mg / L HCO3). -200 ml of the mixture was placed in beakers and labeled 1, 2, and 3. 400 mg / L CuCoO2 was added to beaker 1; 40 mM H2O2 was added to beaker 2; and 40 mg / L CuCoO2 and 40 mM H2O2 were added to beaker 3. The mixture was stirred at 800 rpm, and samples were taken every 20 minutes to measure the concentration of contamination in the groundwater.
[0053] Example 5 Four samples of contaminated groundwater were taken separately (under dark, room temperature conditions; the main components were the contaminating antibiotic (chlortetracycline) and 600 mg / L HCO3). - 200 ml of the mixture was placed in beakers and labeled 1, 2, 3, and 4. For beaker 1, 100 mg / L CuCoO2 and 40 mM H2O2 were added; for beaker 2, 200 mg / L CuCoO2 and 40 mM H2O2 were added; for beaker 3, 300 mg / L CuCoO2 and 40 mM H2O2 were added; and for beaker 4, 400 mg / L CuCoO2 and 40 mM H2O2 were added. Samples were taken every 20 minutes to measure the concentration of contamination in the groundwater.
[0054] Effect test: The CuCoO2 catalyst material prepared in Example 1 was analyzed by X-ray diffraction. Figure 1 As shown.
[0055] from Figure 1 As can be seen from the data, the diffraction peaks of the CuCoO2 catalytic material prepared in Example 1 of this application have a good correspondence with the typical CuCoO2 material phase.
[0056] The CuCoO2 catalytic material prepared in Example 1 was observed using a scanning electron microscope, as shown below. Figure 2 As shown. From Figure 2 As can be seen from the example, the CuCoO2 catalytic material prepared in Example 1 of this application has a hexagonal shape, a larger specific surface area, and can provide more active sites.
[0057] The HCO3 in the stirred solution of Example 2 was detected by nuclear magnetic resonance (NMR). - With HCO4 - ,like Figure 3 As shown. From Figure 3 It can be seen from the use 13 C NMR spectroscopy analysis 13 C-labeled HCO3 - The equilibrium reaction between H2O2 and H2O2 was initially observed at 160.8 ppm. 13 The C symbol corresponds to HCO3 -The characteristic peak of HCO4 appeared at 158.6 ppm as the reaction progressed. - (New characteristic peaks).
[0058] The solution stirred in Example 3 was analyzed by detecting carbonate radicals (CO3•) using p-nitroaniline (PNA) as a probe. - The generation of ), such as Figure 4 As shown. From Figure 4 The results show that p-nitroaniline (PNA) was used as a molecular probe to detect carbonate radicals (CO3•). - In the synergistic system, a large number of carbonate radicals are generated and much of them are consumed within 120 minutes, with no HCO3-. - No carbonate radicals were generated in the system, and no consumption occurred. Figure 5 It is to carry out the development of carbonate free radicals (CO3• - Quenching experiments, such as Figure 5 As shown, DMA is used to quench carbonate radicals (CO3• - The degradation efficiency decreases after that.
[0059] Figure 6 This image shows the degradation effect of CuCoO2 catalyst on doxycycline hydrochloride in contaminated groundwater under different systems in Example 4. From... Figure 6 As can be seen from the data, at a degradation time of 120 min, the degradation efficiency of doxycycline hydrochloride in contaminated groundwater was 3% for sample 1 (containing 400 mg / L CuCoO2), 3% for sample 2 (containing 40 mM H2O2), and 93% for sample 3 (containing both 400 mg / L CuCoO2 and 40 mM H2O2). This demonstrates that the CuCoO2 prepared in this application and the constructed CuCoO2 / H2O... 2 / The NaHCO3 system exhibits good catalytic degradation performance.
[0060] Figure 7 This is a graph showing the degradation effect of different amounts of CuCoO2 catalyst on doxycycline hydrochloride in contaminated groundwater in Example 5. From... Figure 7As can be seen, at a degradation time of 120 min, the degradation efficiency of CuCoO2 at a concentration of 100 mg / L for doxycycline hydrochloride in contaminated groundwater was 68%, that at a concentration of 200 mg / L was 71%, that at a concentration of 300 mg / L was 74%, that at a concentration of 400 mg / L was 93%, and that at a concentration of 500 mg / L was 85%. This indicates that the CuCoO2 prepared in this application exhibits the best degradation efficiency at a concentration of 400 mg / L.
[0061] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.
Claims
1. A method for preparing a bimetallic CuCoO2 heterogeneous Fenton-like catalyst material, characterized in that, Includes the following steps: The bimetallic CuCoO2 heterogeneous Fenton-like catalyst material is obtained by mixing Cu source, Co source, alkali and water and carrying out a hydrothermal reaction.
2. The preparation method according to claim 1, characterized in that, The Cu source is Cu(NO3)2·3H2O.
3. The preparation method according to claim 1, characterized in that, The Co source is Co(NO3)2·6H2O.
4. The preparation method according to claim 1, characterized in that, The alkali is NaOH.
5. The preparation method according to claim 1, characterized in that, The molar ratio of Cu source, Co source and alkali is 1:1:(8~8.5); the ratio of Cu source to water is 15 mmol:(50~70) mL.
6. The preparation method according to claim 1, characterized in that, The hydrothermal reaction conditions are set as follows: 120~180℃ for 6~12 h; after the hydrothermal reaction is completed, the reaction also includes filtration, and the filtered product is washed, dried and ground.
7. A bimetallic CuCoO2 heterogeneous Fenton-like catalyst material prepared by the preparation method according to any one of claims 1 to 6.
8. The application of the bimetallic CuCoO2 heterogeneous Fenton-like catalyst material as described in claim 7 in the in-situ oxidative degradation of organic pollutants in groundwater, characterized in that, HCO4 in the groundwater - The concentration is 500~700mg / L; bimetallic CuCoO2 heterogeneous Fenton catalyst material and H2O2 are added to the groundwater to achieve in-situ oxidative degradation of organic pollutants in the groundwater.
9. The application according to claim 8, characterized in that, The concentration of the bimetallic CuCoO2 heterogeneous Fenton-like catalyst material added to groundwater is 100~600 mg / L, and the concentration of H2O2 added to groundwater is 10~100 mM.
10. The application according to claim 8, characterized in that, The organic pollutant is doxycycline hydrochloride.
